A One-Mass Physical Model of the Vocal Folds with Seesaw-Like Oscillations - QURESHI, Tahir Mushtaq; SYED, Khalid Saifullah (Archives of Acoustics, 2013)
A low-dimensional physical model of small-amplitude oscillations of the vocalfolds is proposed here. The model is a simplified version of the body-cover one inwhich mucosal surface wave propagation has been approximated by the seesaw-likeoscillation of the vocal fold about its fulcrum point whose position is adjustable inboth the horizontal and vertical directions. This approach works for 180 degreephase difference between the glottal entry and exit displacements. The fulcrumpoint position has a significant role in determining the shape of the glottal flow.The vertical position of the fulcrum point determines the amplitude of the glottalexit displacement, while its horizontal position governs the shape and amplitude ofthe glottal flow. An increment in its horizontal position leads to an increase in theamplitude of the glottal flow and the time period of the opening and closing phases,as well as a decrease in the time period of the closed phase. The proposed model isvalidated by comparing its results with the low-dimensional mucosal surface wavepropagation model.